Pemanfaatan Ampas Tahu dan Kayambang dengan Pupuk Kandang Ayam sebagai Amelioran dalam Budidaya Jagung Manis (Zea mays saccharata Sturt) di Tanah Gambut - Yusanti Mantuh (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2018)
This research aims were to find the effect of giving Toffu (Soybean production) Waste and Kayambang with Chicken Manure as The Ameliorant on Growth and Yield of Sweet Corn (Zea mays saccharataSturt) Cultivation in Peat Soil. Then, to find the effect of giving both of Toffu Waste and Kayambang on Growth and Yield of Sweet Corn Cultivation in Peat Soil. Also to find the effect of giving Chicken Manure only on Growth and Yield of Sweet Corn Cultivation in Peat Soil. Moreover, this research design was a field experiment design that was arranged by using Randomized Block Design (RBD) with 2 (two) treatment factors and 3 (three) repetitions. In addition, the factors in this research were: first factor (A) were toffu waste and kayambang with 5 levels, those we:A0 (Without added bytoffuwaste and kayambang), A1 (Toffu waste 5 ton acre-1), A2 (Toffu waste 10 ton acre-1), A3 (kayambang 5 ton acre-1), and A4 (kayambang 10 ton acre-1). While the second factors (B) were chicken manure with 3 levels, those were B0 (without chicken manure), B1 (chicken manure 5 ton acre-1), and B2 (chicken manure 10 ton acre-1). Furthermore, the result of this research showed that the interaction of giving Toffu (Soybean production) Waste and Kayambang with Chicken Manure as The Ameliorant gave the real effect to the ratio of between shoot and root, also the yield of Sweet Corn (Zea mays saccharataSturt), especially in the weight of sweet corn cob with and without its cover, also the diameter of the cob. As the result, the using of toffu waste and kayambang as ameliorant showed high effect to the plant. While the using of chicken manure gave effects to the vegetation growth (plant high, leaves weight, shoot dry weight, roots dried weight) and to the lenght of the sweet corn cob in the harvest time.